Neurosurgical Treatment of Acromegaly - Buchfelder, Michael; Feulner, Julian (Progress in Nucleic Acid Research and Molecular Biology, 2016)
Surgical removal of as much tumor mass as possible is usually considered the first step of treatment in acromegaly, unless the patients are unfit for surgery or refuse an operation. To date, in almost all cases, minimally invasive, transsphenoidal microscopic or endoscopic approaches are used. Whether a curative approach is feasible or a debulking procedure is planned, can be anticipated on the basis of preoperative magnetic resonance imaging. It mostly depends on localization, size, and the invasive character of the lesion. The surgical results depend on tumor-related factors such as size, extension, the presence or absence of invasion, and the magnitude of IGF-1 and growth hormone oversecretion, respectively. However, even surgeon-related factors such as experience and case load of the centers have been shown to strongly affect surgical results and complication rates. A reoperation can be considered at various stages in the treatment algorithm. There are several new technical gadgets which might aid in the surgical procedure: navigation, the Doppler probe, and variants of intraoperative imaging.
EVALuna2:33862